The Value of Technical Services - Corbett, Lauren E. (My University, 2018)
What is the value of the work done in library technical services to researchers, to librarians, to someone using Google? To me, it seems relatively straightfor- ward to help people at the university understand that someone must order, pay for, and make collections avail- able for use. But I also would like to make it clear to people everywhere that there is value added for a larger, even worldwide, community of information- seekers when copy catalogers and cataloging librarians in any library create bibliographic records, make data corrections, or add missing bits of data.
Keywords: technical services; libraries